2014
DOI: 10.1088/0256-307x/31/12/124202
|View full text |Cite
|
Sign up to set email alerts
|

Passive Q-Switching Laser Performance of Yb:YVO 4 Crystal

Abstract: We report on the passive Q-switching laser performance of Yb:YVO4 crystal. Utilizing a Cr 4+ :YAG crystal plate as the saturable absorber, which is of an initial transmission as high as 99.3%, we demonstrate a stable passively Q-switched laser operation at 1017.2 nm, producing an average output power of 0.87 W at a pulse repetition rate of 71.4 kHz, with a slope efficiency of 30%. The resulting pulse energy, duration, and peak power are 12.2 𝜇J, 87 ns, and 0.14 kW, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…As a matter of fact, stable passive Q-switching proves to be very difficult to achieve with a Cr 4+ :YAG absorber of very high initial transmission (T 0 > 99%). So far, stable passive Q-switching induced by a Cr 4+ :YAG absorber of T 0 > 99% has only been realized in Yb:YVO 4 , Yb:LuVO 4 , and Yb:KLuW lasers [24][25][26]. It needs to be pointed out that the pulse trains presented in figure 6 were recorded with quite a long scanning period (1-2 ms), which might lead to some inaccuracy due to the way in which the sampling oscilloscope operates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, stable passive Q-switching proves to be very difficult to achieve with a Cr 4+ :YAG absorber of very high initial transmission (T 0 > 99%). So far, stable passive Q-switching induced by a Cr 4+ :YAG absorber of T 0 > 99% has only been realized in Yb:YVO 4 , Yb:LuVO 4 , and Yb:KLuW lasers [24][25][26]. It needs to be pointed out that the pulse trains presented in figure 6 were recorded with quite a long scanning period (1-2 ms), which might lead to some inaccuracy due to the way in which the sampling oscilloscope operates.…”
Section: Resultsmentioning
confidence: 99%
“…Our experiment showed that no stable passively Q-switched laser operation could be achieved with either Yb:YCOB or Yb:GdCOB under similar conditions. Up to now, the known Yb-ion lasers, which are able to be passively Q-switched by a Cr 4+ :YAG saturable absorber with such a high T 0 , only include Yb:YVO 4 , Yb:LuVO 4 , and Yb:KLuW[24][25][26]. The results for these lasers are also presented in table 1 for comparison.A similar summary is presented in table…”
mentioning
confidence: 99%
“…As ω → −1, the effects of quintessence and cosmological constant will be similar [46]. Moreover, the P V criticality and thermodynamical properties (pressure, volume and Hawking temperature) of quintessential RN-AdS BH is discussed by Li [47].…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide variety of Yb-ion laser crystals developed so far, Yb:YCa 4 O(BO 3 ) 3 (Yb:YCOB) stands out as a very promising laser medium for producing high-energy laser pulses in Q-switched operation. In our recent work on an Yb:YCOB laser passively Q-switched with a Cr 4+ :YAG saturable absorber, a pulse energy of 1.28 mJ was generated at a repetition rate of 3.23 kHz, revealing the great potential of this crystal in making high-energy pulsed lasers [12].…”
Section: Introductionmentioning
confidence: 99%